A Simplified Analytical Solution for the Computation of Machine Path in Filament Winding of Cylindrical Angle-Ply and Double-Double Structures - Andrianov, A.; Militão, A.P.F. (Journal of Research Updates in Polymer Science, 2022)
This paper presents a simplified computation approach for the machine path (or winding trajectory) of grid structures and tubes with a circular cross-section and angle-ply or double-double layup. The solution for the machine path is given through controllable degrees of freedom of a low-cost two-axis filament winding machine (FWM): mandrel rotation and translation of the delivery eye along the axis of the mandrel. The efficiency of the analytical solution for the machine path of the FWM was ascertained by automated laying the cotton thread over the geodesic and non-geodesic groove imprinted on the surface of a cylindrical polylactide mandrel. These results validated the possibility of manufacturing cylindrical composite structures with an angle-ply layup or double-double stacking sequence, without the need for expensive software, making the winding technology accessible to society and promoting university extension.